Aggregate dynamic modelling and optimal control in cellular electric energy systems - Holm Hinners; Sergio F. Contreras; Johanna Myrzik (IET Generation, Transmission & Distribution, 2022)
Abstract The large number of distributed generators, storages, and other devices which might be connected to the distribution grid pose significant modelling and control questions. It is computationally unattractive and sometimes infeasible to model and control all these devices individually; some method of aggregating them both for modelling and for control is appealing so that they can be represented collectively. It would also be preferable to limit the complexity of the controlled devices' dynamic behavior for easy integration with higher‐level (i.e., higher‐authority) controllers in the cascade. This paper describes a method combining these control goals based on geometric flexibility regions, constrained optimization, and transfer function considerations to enforce approximated first‐order transfer function behaviour at the bus. Time‐domain simulations are used for validation and demonstration.